PENERAPAN TEKNOLOGI RECIRCULATING AQUACULTURE SYSTEM (RAS) PADA PEMELIHARAAN BENIH IKAN NILA DI UPR PROGOSARI KOTA TARAKAN - Miska Sanda Lembang; Aan Digita Malik; Noerman Adi Prasetya; Muhammad Rusli; Santria Santria; Diani Aprilastina (Jurnal Abdi Insani, 2023)
A fishery commodity that is in great demand because it contains good nutrition is tilapia. Rearing fish fry is a critical phase that allows many deaths to occur. The death of fry is generally due to the quality of the cultivation water decreasing due to the accumulation of dirt from both food waste and fish feces. In general, the way to overcome this is by changing the water. However, this will not be efficient if done on a large scale. The aim of this activity is to apply Recirculating Aquaculture System (RAS) technology to seed production businesses to minimize water use, maintain water quality and optimal survival of tilapia seeds. The activity method consists of socializing PKM activities, training and mentoring in the application of Recirculating Aquaculture System (RAS) technology. Training and assistance consists of building recirculation ponds, preparing and maintaining filter media, as well as maintaining tilapia fry and measuring water quality. When applying Recirculating Aquaculture System (RAS) technology, the results obtained are that the tilapia rearing pond with a series of RAS systems has been installed properly and is integrated with a drum filter. The filter drum consists of several filters from bottom to top, namely palm fiber, pumice stone, charcoal and bioball. Each filter has its own role as a physical, chemical and biological filter in removing aquaculture waste such as feces and fish food residue. Maintaining tilapia fry by providing food and measuring water quality. The survival result of tilapia seeds was 100% in 20 days of rearing tilapia seeds in recirculation ponds. Based on this activity, it can be concluded that the Recirculating Aquaculture System (RAS) technology pond is able to maintain water quality, increase seed survival even without water changes (water saving).